Phytochemical investigation of extract of Amorphophallus campanulatus tubers - Seema Firdouse; Parwez Alam (International Journal of Phytomedicine, 2011)
Pharmacognostic evaluation of Amorphophallus campanulatus tubers for alkaloids, saponins, coumarins, tannin, steroids, flavones, quinones, proteins phenols, carbohydrates. It was concluded that the extract of tuber contain important constitutents for pharmacological acitivity